25 Years of 3D Ultrasound in Prenatal Diagnosis (1989–2014) - Merz, E. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
25 years of 3 D ultrasound in prenatal diagnosis represent an important milestone in recent ultrasound history. The initial stages of 3 D ultrasound were anything but easy. Although there were reports of initial experimental in-vitro ultrasound studies as early as the 1970s and 1980s 12, clinical use did not begin until the first commercial 3 D ultrasound unit (Combison 330, Kretztechnik Zipf, Austria) was introduced in 1989 (Fig. 1) 34. With this unit it became possible for the first time to produce so-called multiplanar (= triplanar) images. This means that it was possible to display the three orthogonal two-dimensional image planes at the same time on the monitor (Fig. 2). Volume acquisition via a relatively large abdominal 3 D probe, which – in contrast to the 2 D probe – had to be held at a right angle to acquire a longitudinal scan, was unfamiliar (Fig. 3a, b). In contrast to the abdominal 3 D probe that acquired a pyramid-shaped volume with motor-controlled mechanical fan-shaped sweep of the scanning plane, a rotation method was selected for the volume acquisition with the 3 D vaginal probe for reasons of space. However, this had the disadvantage of central overlapping of all sectional planes resulting in limited image quality at the center (Fig. 3c, d). This disadvantage could not be eliminated until it became possible to perform a motor-controlled mechanical fan-shaped sweep of the imaging plane for volume acquisition with the 3 D vaginal probe. The introduction of the so-called surface mode made it possible to visualize surface images of the fetus and embryo with an abdominal as well as a vaginal 3 D probe. Due to the substantial processing power that this required, it initially (1992) took 6 hours to create one surface image with an external computer. Today a surface rendering of one image takes between 20 and 50 milliseconds depending on the volume. Parallel to this so-called internal or integrated system in which the complete 3 D unit is permanently integrated in the ultrasound unit and the 3 D probes are matched to the system (Fig. 4) 5, so-called external 3 D systems (e. g. TomTec, Echotech, InViVo-System), in which acquisitions can be performed using any conventional 2 D probe, were also developed 5. An electromagnetic position sensor must simply be attached to the probe so that the transducer position and movements can be recorded on the basis of changes in the magnetic field (Fig. 4). After transfer of the individual 2 D images to a workstation, the images and their individual positions are assembled by a computer program to form a volume. The disadvantage of external systems is that the distances between the individual two-dimensional image planes are usually not identical due to the manual probe guidance, resulting in a lower volume quality, and that 4 D display is not possible 5.Due to the initial problems with 3 D ultrasound, many experienced 2 D ultrasound operators were initially skeptical of this new technique. Therefore, 3 D ultrasound was viewed as a difficult, inconvenient, and unnecessary method. Typical questions that were repeatedly asked included 4: Is 3 D ultrasound more useful in prenatal diagnosis? Does it improve diagnostic accuracy or is it only good for keepsake images? Can we detect more malformations? Is it useful in the daily routine or is it only time-consuming? This technique continues to be inexplicably disqualified by some examiners as baby television even though three-dimensional ultrasound has found broad use in obstetric diagnosis.There is no doubt that 3 D ultrasound has become widely globally available since the first World Congress on 3 D Ultrasound on September 5 – 6, 1997 in Mainz, Germany (Fig. 5). Different technical developments, such as simplification of operation, faster image rendering due to greater computer processing power, and significant improvement in image quality, contributed to this. Every high-end ultrasound unit is currently equipped with such a technique. Moreover, an increasing number of publications regarding the use of 3 D ultrasound in prenatal diagnosis have appeared since 1997 6789101112131415161718192021222324252627282930. However, proper use of 3 D ultrasound entails a learning curve of several months. Technical know-how, spatial reasoning, and continuous training are helpful for those learning the technique. Finally it must be taken into consideration that every 3 D ultrasound is based on 2 D ultrasound 21 and that high quality 3 D surface images can thus only be achieved in the case of good 2 D image quality and if the fetus is surrounded by sufficient amniotic fluid and there are no obstructing structures 5.A 3 D examination generally consists of four main steps: 1. volume acquisition, 2. 3 D visualization, 3: volume/image processing and 4. storing of volumes/images/sequences 5.In contrast to 2 D ultrasound, 3 D ultrasound provides a number of imaging modes and image processing techniques (Table 1) that are used in prenatal diagnosis depending on the particular issue.With triplanar imaging, all planes can be reconstructed and visualized from one volume and special planes can be controlled in a precise manner on the basis of the two other orthogonal imaging planes. An enormous improvement in image quality has been able to be achieved in the last 2 decades in particular with regard to surface images as well as transparent images ( Fig. 6). Moreover, 4 D ultrasound made it possible to display fetal movements in surface and transparent mode as in a video.3 D/4 D technology has become a valuable supplementary method to conventional 2 D ultrasound in the diagnosis of malformations and can be used by skilled ultrasound operators to clarify suspicious findings in a targeted manner. As a result, the nuchal translucency and nasal bone can be precisely measured in the first trimester. Complex organs, such as the fetal heart 810182224 and the fetal brain 719232526, can be precisely examined tomographically in the second and third trimesters. Heart defects as well as vascular anomalies can be visualized three-dimensionally using color Doppler 182728. 3 D neurosonography is playing an increasingly important role in the detection or exclusion of brain malformations since all planes can be precisely set and an exact comparison between the left and right brain hemispheres is also possible. In the surface mode surface defects of the fetal head (cleft lip and palate/encephalocele) or in other body regions (spina bifida, defects of the abdominal wall or extremities) can be precisely detected 691221. Moreover, skeletal changes or ossification defects can be clearly detected with the X-ray-like imaging of the fetal skeleton in the transparent mode 1213. The detection of subtle changes in fetuses opens up completely new possibilities in the diagnosis of chromosomal disorders 13 and syndromes some of which can only be detected on the basis of discrete sonoanatomical changes.Particularly in the case of the exclusion of fetal malformations, such as facial defects, 4 D surface imaging is an ideal method to reassure parents-to-be since they can personally see fetal movements as well as the normal finding on the monitor 4. Seeing surface images of the fetal face is certainly one of the most impressive moments of the ultrasound examination for parents-to-be. However, providing parents with nice pictures of their unborn child is not the main goal of the examination but rather a byproduct 31.A further significant advantage of 3 D ultrasound for the examiner is that three-dimensional structures are not only shown three dimensionally but can also be digitally stored without loss in the form of 3 D images, volumes, or 3 D sequences 16. The digital storage of volumes permits virtual examinations, i. e., volumes can be reloaded at any time and examined in the absence of the patient 1621. With the help of a special computer program, all stored volumes can also be loaded onto a PC or Notebook and can thus be examined independently of the ultrasound unit. From an educational standpoint, the digital storing and rendering of volumetric data represents a new approach in medical education. Reviewing copies of a stored volume allows several trainees to be taught at the same time to recognize the fetal anatomy hidden within the volume 416.25 years after the introduction of three-dimensional ultrasound in clinical diagnostics, 3 D/4 D ultrasound provides such a broad diagnostic spectrum in the daily routine that it has become a fixture in targeted prenatal diagnosis as well as in the clarification of gynecological findings 2132333435, pelvic floor defects 36, and in breast diagnostics 37. The same is also true for various other areas of specialization 383940.The recently introduced ultrasound device E10 from GE, which uses a fully electronic abdominal probe (matrix probe) and the HDlive Silhouette visualization mode to provide even more impressive ultrasound images of embryonic/fetal development than previously possible, shows that the field of 3 D/4 D ultrasound is continuing to advance. Further developments in the field of computer technology will certainly help to ensure future innovations on the part of ultrasound device manufacturers.